The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1111/j.1095-8649.2012.03290.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic divergence among invasive and native populations ofPlagioscion squamosissimus(Perciformes, Sciaenidae) in Neotropical regions

Abstract: The genetic divergence among invasive and native populations of Plagioscion squamosissimus from four Neotropical hydrographic basins was assessed using the hypervariable domain of the mitochondrial DNA (mtDNA) control region. Plagioscion squamosissimus is native to the neighbouring hydrographic basins of the Parnaíba and Amazon Rivers, and the latter includes the Araguaia-Tocantins drainage, but it is invasive in other basins due to introductions. The mtDNA nucleotide polymorphism supported the hypothesis that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 25 publications
1
9
1
Order By: Relevance
“…In the current study, the genetic variability between native and invasive populations of P. squamosissimus was verified by examining the mtDNA control region across populations. The results were consistent with those from RAPD, and they showed low genetic variability within and among the populations of the floodplain of the upper Paraná River, the Itaipu reservoir, and Parnaíba, and high genetic variability in the populations of the Tocantins River basin (Panarari-Antunes et al, 2012).…”
Section: Discussionsupporting
confidence: 86%
“…In the current study, the genetic variability between native and invasive populations of P. squamosissimus was verified by examining the mtDNA control region across populations. The results were consistent with those from RAPD, and they showed low genetic variability within and among the populations of the floodplain of the upper Paraná River, the Itaipu reservoir, and Parnaíba, and high genetic variability in the populations of the Tocantins River basin (Panarari-Antunes et al, 2012).…”
Section: Discussionsupporting
confidence: 86%
“…In the case of introduced P. squamosissimus populations, others factors may also be related to its successful invasion. P. squamosissimus successfully colonised all the habitats of the Paraná River basin (Agostinho et al, 2008), despite the low genetic diversity rates observed in the current analyses and by Panarari-Antunes et al (2012, 2015.…”
contrasting
confidence: 53%
“…Panarari‐Antunes et al . () revealed that P. squamosissimus offspring from the Parnaíba River basin occur only in the Paraná River basin and these have no kinship with the populations of the Amazon River basin. Thus, their findings support the current results.…”
Section: Collection Sites and Number Of Specimens Plagioscion Squamosmentioning
confidence: 99%
See 1 more Smart Citation
“…Molecular markers have been successfully used for intraspecific genetic divergence studies with invasive species, especially the mitochondrial DNA (mtDNA) control region (CR) (Prioli et al , ; Oliveira et al , ; Fitzpatrick et al , ; Panarari‐Antunes et al , ; Willis et al , ; Gasques et al , ). The mtDNA CR is much more variable than nuclear DNA loci ( e.g .…”
Section: Introductionmentioning
confidence: 99%